Trends in undergraduate economics degrees, 1991–2016. Issue 3 (3rd July 2017) - Siegfried, John J.
ABSTRACT: Undergraduate degrees awarded in economics by U.S. colleges and universities were stagnant from 2009–10 through 2012–13, increased rapidly (almost 15 percent) over the two years from 2012–13 through 2014–15, but have again leveled off in 2015–16.